State Institutional Law: Dualism in the Development of the Tax Court in Indonesia Between the Supreme Court and the Ministry of Finance - Yunus, Nur Rohim (UIN JAKARTA, 2023)
This article discusses the dualism in developing the Tax Court in Indonesia, which involves the Supreme Court and the Ministry of Finance. The research background includes the complexity of the tax justice system and challenges in coordination between the two institutions. The aim of the research is to identify the benefits, weaknesses and potential risks of this dualism coaching system. The research method used is qualitative with a literature and legislation approach to analyze the legal framework and its practical implementation. The research results show that the dualism coaching system provides a variety of approaches, but also creates the potential for conflict, uncertainty and waste of resources. This article concludes by stating the importance of improving coordination between the Supreme Court and the Ministry of Finance in order to increase efficiency and effectiveness in developing the Tax Court and ensuring legal certainty in resolving tax disputes in Indonesia.